2011
DOI: 10.1007/s00382-011-1261-4
|View full text |Cite|
|
Sign up to set email alerts
|

Future projections of the surface heat and water budgets of the Mediterranean Sea in an ensemble of coupled atmosphere–ocean regional climate models

Abstract: Within the CIRCE project "Climate change and Impact Research: the Mediterranean Environment", an ensemble of high resolution coupled atmosphere-ocean regional climate models (AORCMs) are used to simulate the Mediterranean climate for the period 1950-2050. For the first time, realistic net surface air-sea fluxes are obtained. The sea surface temperature (SST) variability is consistent with the atmospheric forcing above it and oceanic constraints. The surface fluxes respond to external forcing under a warming cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 76 publications
10
79
1
1
Order By: Relevance
“…The eddy-permitting model, with its higher horizontal resolution, more vertical levels and more accurate surface process parameterizations than CMCC-CM, allows a better representation of the Mediterranean dynamics, with a positive feedback on SST simulation. The cold bias of CMCC-CM is clearly reduced by CMCC-MED everywhere, especially in the central and northern part of the basin, but it is still around 2 • C. On the other hand, Dubois et al (2012) found that all CIRCE models simulate SSTs (and air temperatures) that are cooler than the observations. Such a shortcoming encompasses several reasons, ranging from radiative forcings to the marine albedo, but the problem is still under debate and a clear understanding of its reasons is still missing.…”
Section: Effect On Sst Climatologymentioning
confidence: 78%
See 2 more Smart Citations
“…The eddy-permitting model, with its higher horizontal resolution, more vertical levels and more accurate surface process parameterizations than CMCC-CM, allows a better representation of the Mediterranean dynamics, with a positive feedback on SST simulation. The cold bias of CMCC-CM is clearly reduced by CMCC-MED everywhere, especially in the central and northern part of the basin, but it is still around 2 • C. On the other hand, Dubois et al (2012) found that all CIRCE models simulate SSTs (and air temperatures) that are cooler than the observations. Such a shortcoming encompasses several reasons, ranging from radiative forcings to the marine albedo, but the problem is still under debate and a clear understanding of its reasons is still missing.…”
Section: Effect On Sst Climatologymentioning
confidence: 78%
“…It is worth noticing that the improved information due to the very high resolution of MFS is partly deteriorated in the coupling procedure by averaging the SST over the coupling frequency time and by interpolating the field to the coarse atmospheric model. On the other hand, Dubois et al (2012), examining the performances of CIRCE models in terms of surface heat and water budgets over Mediterranean Sea, showed that the presence of an underlying marine model, which realistically simulates the small-scale spatial structures over the Mediterranean, is still beneficial in terms of the air-sea interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncertainty related to the choice of the GCM or ARCM or ORCM has been partially tackled in CIRCE (Gualdi et al 2013;Dubois et al 2012) and a larger multi-model exercice is currently being organised under the umbrella of the Hymex, Med-CORDEX and Med-CLIVAR programs.…”
Section: Initial Conditions Spin-up and Runsmentioning
confidence: 99%
“…A review of the studies dealing with Mediterranean climate projections is presented in Planton et al (2012). The regional coupled models intercomparison study by Dubois et al (2012) presented Mediterranean Sea projections under A1B scenario for 1950-2050 and found a decrease in the heat loss and an increase in water loss over the ocean, which may strongly impact the Mediterranean water masses and the associated MTHC. A recent study by Lazzari et al (2013) investigated the impact of A1B climate change scenario on the Mediterranean trophic regimes, but their time slice approach presented some limitations compared to the transient approach of the CIRCE project simulations (Gualdi et al 2013), with smaller SST increase at the end of the twenty-first century compared to other studies.…”
mentioning
confidence: 99%